Risk of Venous Thromboembolism in Acute Necrotizing Pancreatitis: A Large Database Study. Issue 1 (January 2021) - Ahmad, Dina S.; Mansoor, Emad; Alikhan, Muhammed M.; Rana, Mariam Nadeem; Panhwar, Muhammad Siyab; Wong, Richard C.K.; Smith, Zachary L.
Abstract : Objectives: Studies on the incidence of venous thromboembolism (VTE) in acute pancreatitis (AP) are scarce. We conducted a large database study to evaluate this relationship. Methods: Data were extracted from a large electronic health record (Explorys; IBM Watson Health, Armonk, NY). We identified patients with AP in 2018 and 2019, analyzing VTE incidence at 30 days after diagnosis of AP. Univariate and multivariate analyses were performed to identify risk factors associated with VTE. Results: A total of 25, 620 cases of acute necrotizing pancreatitis (ANP) and 155, 800 cases of acute nonnecrotizing pancreatitis (ANNP) were identified. The incidence of VTE was 7.1% for ANP, compared with 2.8% in ANNP ( P < 0.001). On multivariate analysis, ANP conferred significantly greater odds of VTE (adjusted odds ratio, 2.78; 95% confidence interval, 2.73–2.84; P < 0.001), independent of other variables. In those with ANP, the presence of VTE was associated with a significantly higher mortality (23.5% vs 15.9%, P < 0.001). Conclusions: Acute necrotizing pancreatitis carries near 2.5-fold risk of VTE, and a 3-fold risk of PE, compared with those with ANNP. Venous thromboembolism development in ANP is associated with higher mortality. Abstract : Supplemental digital content is available in the text.